Role of the Neutrophil Chemorepellent Soluble Dipeptidyl Peptidase IV in Decreasing Inflammation in a Murine Model of Arthritis. Issue 10 (23rd September 2015) - Herlihy, Sarah E.; Brown, Monica L.; Pilling, Darrell; Weeks, Brad R.; Myers, Linda K.; Gomer, Richard H.
Abstract : Objective: To determine whether an intraarticular injection of the neutrophil chemorepellent dipeptidyl peptidase IV (DPPIV; CD26) can attenuate inflammation and decrease the severity of arthritis in a murine model. Methods: DBA/1 mice were immunized with type II collagen/Freund's complete adjuvant to produce collagen‐induced arthritis (CIA). On day 25 postimmunization, recombinant human DPPIV (rhDPPIV) or phosphate buffered saline was injected intraarticularly, and arthritis severity scores were recorded 3 times per week. The hind legs of mice in both groups were fixed, decalcified, paraffin embedded, and sectioned. Pathologic scores for inflammation and neutrophil infiltration were recorded on a scale of 1–8, and the number of neutrophils was determined by morphometric cell counts. In addition, Mac‐2–positive macrophages and articular damage were assessed using anti–Mac‐2 antibodies and histologic staining, respectively. Results: Injection of rhDPPIV reduced the mean score of arthritis severity in mice with CIA. DPPIV treatment reduced the overall extent of inflammation and articular damage around the arthritic joint and periarticular tissue, and also decreased neutrophil and macrophage infiltration. Conclusion: A localized injection of the neutrophil chemorepellent DPPIV reduces inflammation and the severity of the disease in a murine model of arthritis.